(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The article examines the decision of the Italian Constitutional court no. 242/2019, pronounced by the Court in the famous case “dj Fabo – Marco Cappato”. It highlights the particular relationship that this decision establishes with the ord. n. 207/2018 (which preceded it), creating an innovative procedural solution not without problems yet to be clarified. However, the comment also addresses the substantive content of the decision. In fact, this decision declares the partial constitutional illegitimacy of the rule punishing the suicide aid of patients who are subject to the particular conditions indicated by the Court. At the same time, the decision establishes a principle that seems to go beyond what is allowed by the Constitutional Court. Considering this scenario, the article highlights – point by point – strengths and weaknesses of the decision also stressing several key aspects that remain to be clarified.